FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ARTHRITIS RHEUMOTOID PADA LANSIA DEWASA MUDA DI WILAYAH KERJA PUSKESMAS RATU AGUNG KOTA BENGKULU - Halizan, Jonri (UNIVED Press, Universitas Dehasen Bengkulu, 2018)
Arthritis RheumotoidCases in Bengkulu City in 2016 that arthritis sufferers occupy all 5 levels similar to Athritis Rheumotoid with 7.889 inhabitants. This study aimed to determine the factors associated with the occurrence of Arthritis Rheumotoid at Ratu Agung Health Center in the city.Thesamples of this study were taken by using an accidental sampling, 69 young adult elderly visiting the health center. The data were collected through direct interview techniques using a questionnaire. The data analysis was done using Univariate and Bivariate analysis with chi-square test at Î± 5%.The results showed that most of the elderly knowledge 49 (71.0%) were sufficient, the majority of the elderly 38 people (55.0%)were female, and almost half of the elderly 30 (43.4%) had medium activity, mostly that no genetically by 37 elderly (54.0%).Most elderly young adults of 39 elderly (56.5%), almost half of the elderly who did not have Arthrtitis Rheumotoid 30 elderly people (43.5%). From the results of the chi-square p = 0.017, 0.031, 0.017, 0.002, and 0.002. Showed no relationship between knowledge, sex, activity, genetic events on the elderly with Arthritis Rheumotoid at Ratu Agung Health Center in the city.The health center is expected to increase to provide more information about Arthritis Rheumotoid in improving the health status of the elderly young adults.